Uji Aktivitas Antibakteri “Ekstrak Metanol Daun Sungkai (Peronema canescens Jack) Terhadap Bakteri Propionibacterium acnes. - Shelin Shelin; Fitriyanti Fitriyanti; Muhammad Saufi (BORNEO JOURNAL OF PHARMASCIENTECH, 2023)
The Sungkai plant (P. canescens Jack) is known to have medicinal properties in the traditional treatment of skin diseases. The aim of this research is to identify groups of phytochemical compounds contained in the methanol extract from Sungkai leaves, as well as evaluate the ability of the methanol extract to inhibit the growth of P. acnes bacteria. In the first stage, phytochemical screening was carried out from the methanol extract of Sungkai leaves. The results of this screening show that the methanol extract of Sungkai leaves contains alkaloids, flavonoids, phenols, triterpenoids and tannins. In the antibacterial activity test, the diffusion method with the well technique was used at extract concentrations of 1%, 5%, 10%, 15% and 20%. As a comparison, the positive control used clindamycin with a concentration of 2 µg/disk, while the negative control used Na-CMC with a concentration of 0.5%. The results of the antibacterial activity test showed that at a concentration of 1%, the methanol extract of Sungkai leaves had an inhibition zone with moderate intensity. However, at a concentration of 20% as well as in the positive control clindamycin with a concentration of 2 µg/disc, there was a stronger zone of inhibition. Thus, these findings indicate that methanol extract from Sungkai leaves has the potential to inhibit the growth of P. acnes, which is often associated with skin problems. The phytochemical compounds contained in this extract can be the basis for potential development in natural-based skin